2005
DOI: 10.1021/jo050595m
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of Chiral Homo- and Heterotrisoxazolines. Improving the Enantioselectivity in the Asymmetric Michael Addition of Indole to Benzylidene Malonate

Abstract: A simple approach to a diverse set of chiral trisoxazolines is described. Deprotonation of bisoxazolines 2, followed by treatment of 2-chloromethyloxazolines 3, affords chiral trisoxazolines, including chiral homo- and hetero-trisoxazolines in good to high yields. These trisoxazolines are successfully applied in the asymmetric reaction of indole with benzylidene malonate, and ee's up to 93% were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…In all cases polyolefins with M w /M n values of between 1.58 and 2.08 were obtained and isotacticities of 80-95 % determined by 13 C NMR spectroscopy ( Figure 6). …”
Section: Trialkyl Complex [Sc(ipr-trisox)a C H T U N G T R E N N U N mentioning
confidence: 86%
See 3 more Smart Citations
“…In all cases polyolefins with M w /M n values of between 1.58 and 2.08 were obtained and isotacticities of 80-95 % determined by 13 C NMR spectroscopy ( Figure 6). …”
Section: Trialkyl Complex [Sc(ipr-trisox)a C H T U N G T R E N N U N mentioning
confidence: 86%
“…Tang and co-workers have found that such potentially tricoordinating ligands may provide Cu-based Lewis acid catalysts that display a significantly improved performance in comparison to the bisoxazoline reference system. [13] However, the role of the "sidearm" is not always clear, [13,14] and a separation of the influence of the BOX-unit and the third "ligand arm" is only meaningful if the metalligand bonding of these components differs significantly. On the other hand, upon going to C 3 -chiral tripods, all three possible ligating units become equivalent, effectively giving up the sidearm notion as discussed above.…”
Section: Designing Chiral Stereodirecting Ligands Based On a Tripod Tmentioning
confidence: 99%
See 2 more Smart Citations
“…The C3-symmetric trisoxazoline 121a-copper(ClO 4 ) 2 · 6H 2 O complex, as a catalyst, is an air-and water-stable compound (Scheme 34) [108][109][110].…”
Section: Scheme 33mentioning
confidence: 99%